Lead-germanate glasses and fibers: A practical alternative to tellurite for nonlinear fiber applications - Munasinghe, H. Tilanka; Winterstein-Beckmann, Anja; Schiele, Christian; Manzani, Danilo [UNESP]; Wondraczek, Lothar; Shahraam Afshar, V.; Monro, Tanya M.; Ebendorff-Heidepriem, Heike (Optica Publishing Group, 2013)
We report on the fabrication of novel lead-germanate glasses and fibers. We have characterized these glasses in terms of their thermal properties, Raman spectra and refractive indices (both linear and nonlinear) and present them as viable alternatives to tellurite glasses for applications requiring highly nonlinear optical fibers. © 2013 Optical Society of America.
Keywords: Glasses In; Non-linear fiber; Non-linear optical fibers; Tellurite glass; Nonlinear optics; Optical fiber fabrication; Optical fibers; Refractive index; Tellurium compounds; Glass